Common Vetch a new threat to rice-fallow pulses in coastal Andhra Pradesh - Ramana, A. V.; Sravanthi, S.; Hemalatha, K. (Indian Farming, 2018)
Even though, the findings of the current study were emanated from an observational trial conducted in the most seriously Vicia sativa infested locations in the farmers’ fields, the results obtained from the study were found to be of great significance and paves way for a systematic investigation to generate valuable information through structured field experimentation.